Enhanced Activity for Methanol Oxidation of Platinum Particles Supported on Iridium Oxide Modified Boron‐Doped Diamond Powder. Issue 8 (21st April 2017) - Preda, Loredana; Kondo, Takeshi; Spataru, Tanta; Marin, Mariana; Radu, Mihai; Osiceanu, Petre; Fujishima, Akira; Spataru, Nicolae
Abstract: Electrocatalytic activity toward methanol oxidation in alkaline media of platinum nanoparticles supported on iridium oxide modified boron‐doped diamond powder (Pt/IrO2 /BDDP) was assessed, and was compared with that of Pt deposited on bare diamond particles (Pt/BDDP). Cyclic voltammetry attests that the presence of the iridium oxide intermediary layer promotes methanol oxidation and provides a more efficient reactivation of Pt particles. Linear sweep voltammetric experiments performed in methanol‐free solution indicated that, at Pt/IrO2 /BDDP, oxygen evolution is preceded by the formation, within the potential range of CH3 OH oxidation, of adsorbed oxygenated species. As expected, the presence in close proximity of Pt particles of such species and of an important amount of IrOx (OH)y (evidenced by XPS) assists in the oxidative desorption of CO species adsorbed on Pt active sites. Steady‐state polarization measurements carried out in a floating configuration with Pt/IrO2 /BDDP gas‐diffusion‐type electrodes yielded for methanol oxidation overall process Tafel slope values of ca. 120 mV decade −1, which compare well with those reported for traditional electrocatalysts. Abstract : Diamond in the rough : A substrate consisting of surface boron‐doped natural diamond powder modified with iridium oxide confers on the supported Pt particles excellent activity for MeOH oxidation in alkaline media. The readiness with which adsorbed oxygenated species are formed on the oxide surface during this process greatly improves the resistance to CO poisoning of the electrocatalyst.